Association between SLCO1B3 gene polymorphism and prostate cancer risk: A meta-analytic study - Shen, Qunshan; Liang, Yu; Li, Haibo; Chen, Mei; Zhang, Jun; Feng, Pengcheng; Meng, Jie; Yu, Haiyun (Bangladesh Journal of Pharmacology, 2018)
The aim of this meta-analysis was to assess the association between SLCO1B3 gene polymorphism and prostate cancer risk. PubMed, Embase, Cochrane Library, and Web of Science from inception to September 2017 were searched. Three authors independently selected studies, extracted data and assessed risk of bias. 5 articles published from 2008 to 2013 with 840 patients were included in this meta-analysis and were from Japan, USA and China. The prostate cancer risk of SLCO1B3 (rs4149117, GG) was markedly higher than that of SLCO1B3 (rs4149117, TT/TG, RR= 0.44, 95%CI: 0.39-0.49, p<0.00001), rs4149117 (TT, RR= 0.37, 95%CI: 0.32-0.42, p<0.00001) and rs4149117 (TG, RR= 0.07, 95%CI: 0.05-0.10, p<0.00001). 2 or 5 years risk free symptoms (RFS) of prostate cancer patient with SLCO1B3 (rs4149117, GG) was markedly higher than that of SLCO1B3 (rs4149117, TT/TG) (RR= -0.17, 95% CI: -0.27–0.07, p= 0.001 and RR= -0.08, 95% CI: -0.16-0.00, p= 0.004). However, no evidence showed there existed significant statistical relationship between SLCO1B3 (rs4149117) and 10 years RFS of prostate cancer (RR= -0.07, 95% CI: -0.19-0.06, p= 0.29). These data suggest that SLCO1B3 (rs4149117, GG) enhanced the RFS of prostate cancer.